Solubility data in radioactive waste disposal - Wanner, Hans (Pure and applied chemistry, 2007)
Radioactive waste arises mainly from the generation of nuclear power but also from the use of radioactive materials in medicine, industry, and research. It occurs in a variety of forms and may range from slightly to highly radioactive. It is a worldwide consensus that radioactive waste should be disposed of in a permanent way which ensures protection of humans and the environment. This objective may be achieved by isolating radioactive waste in a disposal system which is located, designed, constructed, operated, and closed such that any potential hazard to human health is kept acceptably low, now and in the future. For highly radioactive waste and spent nuclear fuel, which are the waste types representing the highest potential danger to human health, an effective isolation from the biosphere is considered to be achievable by deep geological disposal. Disposal concepts rely on the passive safety functions of a series of engineered and natural barriers. Since total isolation over extended timescales is not possible, radionuclides will eventually be released from the waste matrix and migrate through the engineered and natural barriers. The assessment of their mobility in these environments is essential for the safety demonstration of such a repository. The solubility of many radionuclides is limited and may contribute significantly to retention. Reliable predictions of solubility limitations are therefore important. Predictions of maximum solubilities are always subject to uncertainties. Complete sets of thermodynamic and equilibrium data are required for a reliable assessment of the chemical behavior of the radionuclides. Gaps in the thermodynamic databases may lead to erroneous predictions. Missing data and insufficient knowledge of the solubility-limiting processes increase the uncertainties and require pessimistic assumptions in the safety analysis; however, these are usually not detrimental to safety owing to the robustness of the multi-barrier approach.